Effects of MgO particle size and density on microstructure development of MgO based composite phase change materials. (February 2019) - Li, Qi; Li, Chuan; Qiao, Geng; Zhao, Yanqi; Huang, Yaoting; Peng, Xiaodong; Lei, Xianzhang; Ding, Yulong
Abstract: This paper concerns the effects of MgO particle size and density on microstructure development of MgO based composite phase change materials (CPCMs) made of a eutectic carbonate salt of NaLiCO3 (phase change material, PCM), MgO (ceramic skeleton material, CSM) and graphite flakes (thermal conductivity enhancement material, TCEM). Such composite has a melting point around 500 °C and offers a great potential for medium and high temperature thermal energy storage applications including peak shaving of power grids, effective use of curtailed wind energy and solar thermal power generation. Two CPCMs, a light MgO based CPCM and a heavy MgO based CPCM were prepared and investigated. Scanning electron microscopy with energy dispersive X-ray spectrometry (SEM-EDS) was used to measure salt distribution and redistribution within the composite structure during melting-solidification thermal cycles. The results showed that smaller MgO particles yielded smaller internal pores and more rigid/compact composites, leading to better encapsulation of PCM and structural stability through thermal cycles. Concerning the effect of MgO density, the higher surface energy of light MgO induced better particle rearrangement, coarsening and composite densification compared to heavy MgO. These phenomena translated into excellent rigidity, strength and PCM encapsulation. The observation results also showed that the increasing size-similarity between MgO, PCM and graphite leaded to better distribution of components before and after sintering. Upon heating 5 µm sized MgO composites, strong capillary action due to narrow pores, surface energy and MgO distribution, caused excellent PCM migration and graphite distribution. The opposite was observed in large MgO-size composites, which developed large internal voids after initial sintering.